Evaluation of related factors in the failure of endodontically treated teeth: A cross-sectional study - Olcay, Keziban; Ataoğlu, Hanife; Belli, Sema (Elsevier Science Inc, 2018)
Introduction: The aim of this study was to review the factors related to the failure and extraction of unsuccessful endodontically treated teeth. Methods: A total of 1000 teeth treated with nonsurgical root canal therapy were analyzed, and the following information was recorded for each patient: reasons for failure and extraction, type of tooth, presence and type of coronal restoration, smoking status, age, gender, and level of education. One main reason was recorded for each failed tooth. The associations between reasons for failure, patient, and tooth were tested by using chi(2) analysis. Results: Of the 1000 endodontically failed teeth analyzed in this study, 28.1% (n = 281) were extracted, 66% (n = 660) were re-treated, and 5.9% (n = 59) were treated with apical surgery. Among the reasons for failure, restorative and endodontic reasons were seen most frequently (43.9%, n = 439), whereas orthodontic reasons were seldom seen (0.1%, n = 1). The most common reason for extraction was for prosthetic reasons (40.8%), and perforation/stripping was the least common (2.9%). The mandibular first molars were the most frequently extracted teeth (27.4%, n = 77). Conclusions: The most common reason for the extraction of endodontically treated teeth was for prosthetic reasons. Among the reasons for failure, restorative and endodontic reasons were the most frequently seen, and orthodontic reasons were the most seldom. The teeth that failed most frequently were mandibular first molars, and the teeth that failed least frequently were maxillary third molars. The most common reason for the extraction of failed endodontically treated teeth was for prosthetic reasons.
WOS: 000418878600007
PubMed ID: 29246376
Keywords: Endodontically Treated Teeth; Extraction; Failure; Retreatment; Root Canal Treatment